2012
DOI: 10.2176/nmc.52.525
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Puncture Embolization of Scalp Arteriovenous Fistulae

Abstract: We present our experience of flow control with the aid of a circular compression device (CCD) for embolization of scalp arteriovenous fistulae (sAVFs). A 21-year-old female presented with a pulsating scalp mass with sAVFs fed by the superficial temporal arteries. A CCD with a beveled circular handle and concentric hole was used to treat the condition. After the CCD was compressed over the area of the fistulae, the fistulae were punctured and blood regurgitation was assured. While maintaining flow stasis within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The etiology of the AVF of the scalp is still controversial, however, it may be either of congenital or traumatic origin. Among 64 patients with the AVF of the scalp reported in previous research 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 21 22 23) , 36 patients had the traumatic origin. Traumatic origin splits into incidental injury (28 patients) and iatrogenic injury (8 patients).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The etiology of the AVF of the scalp is still controversial, however, it may be either of congenital or traumatic origin. Among 64 patients with the AVF of the scalp reported in previous research 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 21 22 23) , 36 patients had the traumatic origin. Traumatic origin splits into incidental injury (28 patients) and iatrogenic injury (8 patients).…”
Section: Discussionmentioning
confidence: 92%
“…However, excision of secondary scalp venous dilatation without treatment of the intracranial component can be life-threatening 19) . Other therapeutic methods, such as ligation of feeding vessels, transarterial and transvenous embolization 5 9 10 13 23) , and injection of sclerosing agent 21) have been used to treat AVF. In the reported case, we choose the surgical method because of the cosmetic issue and the probability of recurrence with other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major point of endovascular therapy is to obstruct the abnormal arteriovenous shunt. Various intravascular approaches including transarterial, transvenous, and direct puncture for the remedy of sAVF have been reported in the recent literature [ 1 , 5 , 13 , 16 , 17 ]. The advantages of endovascular embolization are small trauma and quick recovery, but for many large supply arteries and draining veins, it is easy to recur after embolization, and the operation cost is high.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the five patients treated by a combination of endovascular treatment + surgical treatment were free of recurrence or complications. 11) Various endovascular procedures have been reported, embolic agents such as Onyx, NBCA, coils, polyvinyl acetate, and ethanol have been used, and techniques including direct puncture using a circular compression device (CCD) 12) and transvenous embolization by Onyx injection using a balloon 13) have been reported.…”
Section: Discussionmentioning
confidence: 99%